Uncommon presentations of enteric fever: A report of three cases - Ruhi Khan; Sruthi Ramindla; Saif Quaiser; Kaynat Khan (Asian Pacific Journal of Tropical Medicine, 2025)
Rationale: Enteric fever is a major public health problem in developing and underdeveloped counties. Extraintestinal manifestations in typhoid are estimated in 27% cases and are associated with severe and complicated diseases. Patients concerns: We report three cases of enteric fever with rare extra intestinal manifestations. Diagnoses: Enteric fever with acute motor-sensory axonal neuropathy, enteric fever with myocarditis, and enteric fever with splenic vein thrombosis. Interventions: All patients were treated with antibiotics. Additionally, Patient 1 was treated with IV immunoglobulin; Patient 2 was treated with vasopressors and anti-cardiac remodeling drugs like ramipril and metoprolol; Patient 3 was treated with anticoagulation with low molecular weight heparin. Outcomes: All patients improved clinically and were followed up on outpatient. Lessons: The diagnosis of enteric fever is challenging and there is an urgent need for prompt-targeted management for better outcomes. Especially in endemic zones and in non-endemic zones as a disease of emporiatric significance.